Bahasa Inggris - Tria Astika Endah Permatasari; Yudi Chadirin; Ernirita; Anisa Nurul Syafitri; Devina Alifia Fadhilah (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Food consumption behavior and home sanitation can be important predictors in the early implementation of stunting detection in toddlers. Stunting is a condition in which a child's physical growth and development are chronically stunted due to malnutrition and inadequate care. This study aims to determine food consumption behavior and home sanitation as predictors in the initial application of stunting detection. This study used a cross-sectional study on 245 children aged 0-59 months who lived in Bogor Regency who were selected using a proportional random sampling technique. Stunting is measured using an anthropometric index (length/height for age). Measuring food consumption using quantitative food intake (food frequency questionnaire) and home sanitation includes indicators of a healthy home, namely cleanliness of floors, walls, ceilings, roof height, function of living rooms, and kitchen space. Sociodemographic characteristics were measured using a structured questionnaire. The prevalence of stunting children under five is 20.4% and the dominant factor for stunting is age (p-value <0.001; AOR=0.254; 95% CI=0.120-0.541). Food consumption and home sanitation are not related to stunting (p-value >0.05). Through a comprehensive approach to food consumption behavior and home sanitation, it is hoped that early prevention and effective interventions for stunting in toddlers can be carried out. Children aged <24 months are more prevented from experiencing stunting 0.254 times than those aged ≥ 24 months.